Methodological aspects of using essential oils in training young sprinters - Popov M.V.; Ushakova I.A.; Sentyabrev; Kamchatnikov A.G. (Theory and Practice of Physical Culture, 2025)
Objective of the study was to based on the evaluation of the impact of essential oils on the physical condition and athletic abilities of athletes, we aim to create a framework for incorporating essential oils into the training regimen of young sprinters. Methods and structure of the study. The state of the muscles in terms of their functional activity was evaluated based on myotometry data. Additionally, specific performance indicators were measured, such as the maximum time for bicycle ergometric work at PWC170 power and the time taken to run a control distance of 100 meters. Using video recording, the running step indicators were measured on segments of 30-40 meters and 80-90 meters. The results were analyzed using the Dartfish computer program (Switzerland). The program calculated the running speed V, the time for each step T, the reference time t, the flight time tp, the frequency of steps (pace) f, and their length l. Results and conclusions. The impact of essential oils enhanced the capacity for muscle relaxation while preserving the ability to reach peak performance. The maximum time spent on the bicycle ergometer increased at the PWC170 level. The time taken for the control run at a distance of 100 meters was improved. This was due to positive changes in the parameters of the running stride at the end of the distance, which helped maintain the running speed. The study identified a set of guidelines for the use of essential oils in training, and based on this, an algorithm and methodology for the use of essential oils in the training of young short-distance runners were developed, tailored to their specific needs. Subsequent experimental validation confirmed the efficacy of the proposed approach.